Reproducibility of functional aortic analysis using magnetic resonance imaging: the MESA. (10th September 2015) - Noda, Chikara; Ambale Venkatesh, Bharath; Ohyama, Yoshiaki; Liu, Chia-Ying; Chamera, Elzbieta; Redheuil, Alban; Teixido-Tura, Gisela; Chugh, Atul R.; Wu, Colin O.; Hundley, Gregory W.; Bluemke, David A.; Lima, Joao A.C.
Abstract: Aims: To assess the test–retest, intra- and inter-reader reliability of thoracic aorta measurements by magnetic resonance imaging (MRI). Methods and results: Twenty-five participants underwent aortic MRI twice over 13 ± 7 days. All aortic variables from baseline and repeat MR were analysed using a semi-automated method by the ARTFUN software. To assess the inter-study reproducibility of aortic variables, we calculated intraclass correlation coefficient (ICC) for individual aortic measurements. Intra- and inter-observer variability was also assessed using the baseline MR data. Mean ascending aortic strain had moderate inter-study reproducibility (11.53 ± 6.44 vs. 10.55 ± 6.64, P = 0.443, ICC = 0.53, P < 0.01). Mean descending aortic strain and arch pulse wave velocity (PWV) had good inter-study reproducibility (descending aortic strain: 8.65 ± 5.30 vs. 8.35 ± 5.26, P = 0.706, ICC = 0.74, P < 0.001; PWV: 9.92 ± 4.18 vs. 9.94 ± 4.55, P = 0.968, ICC = 0.77, P < 0.001, respectively). All aortic variables had excellent intra- and inter-observer reproducibility (intra-: ICC range, 0.87–0.99, inter-: ICC range, 0.56–0.99, respectively). Conclusion: Inter-study reproducibility of all aortic variables was acceptable. Intra- and inter-observer reproducibility of all aortic variables was excellent. MRI can provide a repeatable method of measuring aortic structural and functional parameters.